Два типа рудной минерализации золото-полиметаллического рудопроявления Балки Широкой (Среднее Приднепровье) - Фомин, Ю.А.; Демихов, Ю.Н.; Лазаренко, Е. Е.; Блажко, В.И. (Видавничий дім "Академперіодика" НАН України, 2007)
Quartz-polymetal mineralization in volcanic metasomatites (propylites) (1) was transformed by
a metamorphism (530–450 ◦
С) which destroyed the ﬂuid inclusion system and disturbed the
sulfur isotope equilibrium in sulﬁdes. The Au−Ag−Pb−Zn ores in beresites (2) were formed
by the post metamorphic activity with generation of the epithermal regressive sulﬁde-bearing
system close to the equilibrium temperature range 420–110 ◦
С. In view of the difference in
tendencies for the 34
S content to vary in ore systems, the inversion of ore-forming conditions
from the oxidizing (1) to restoring (2) ones took place.